Examining the Impact of Servant Leadership on Team Innovation: The Mediating Role of Organizational Identification in Sports Psychology - Xiaofei Wang; Yuchun Sun, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Servant leadership, unlike traditional hierarchical models, emphasizes a values-driven approach that fosters positive leadership dynamics. This study investigates the relationship between servant leadership and exploratory innovation within organizations, using organizational identification as a mediating factor. A conceptual model is constructed, hypothesizing that servant leadership positively influences exploratory innovation and that organizational identification plays a critical intermediary role. The study also examines the moderating effects of organizational support for innovation and organizational flexibility. Data were collected from 312 valid questionnaires distributed across high-tech enterprises, including sectors such as Internet software, biomedical technology, electronic information, and new energy industries. The model was validated using SPSS21 and AMOS24 software. The results indicate that servant leadership and organizational identification significantly enhance exploratory innovation. Additionally, organizational identification mediates the relationship between servant leadership and innovation. Organizational support for innovation strengthens the link between servant leadership and organizational identification, while organizational flexibility amplifies the positive relationship between organizational identification and exploratory innovation. In the context of sports organizations, these findings highlight the importance of servant leadership in fostering innovation and team adaptability. By cultivating strong organizational identification and providing robust support structures, sports teams and organizations can enhance their ability to innovate, adapt, and succeed in dynamic environments. These insights underscore the critical role of leadership styles in driving creativity and performance in sports settings.